Label-Free Detection of Cancer Biomarkers Using an In-Line Taper Fiber-Optic Interferometer and a Fiber Bragg Grating - Dandan Sun; Yang Ran; Guanjun Wang (Sensors, 2017)
A compact and label-free optical fiber sensor based on a taper interferometer cascaded with a fiber Bragg grating (FBG) is proposed and experimentally demonstrated for detection of a breast cancer biomarker (HER2). The tapered fiber-optic interferometer is extremely sensitive to the ambient refractive index (RI). In addition, being insensitive to the RI variation, the FBG can be applied as a temperature thermometer due to its independent response to the temperature. Surface functionalization to the sensor is carried out to achieve specific targeting of the unlabeled biomarkers. The result shows that the proposed sensor presents a low limit-of-detection (LOD) of 2 ng/mL, enabling its potentials of application in early diagnosis on the breast cancer.